Community Resiliance and Implications for Waste Management on the Coast of West Aceh: The Existence of Beach Cleaning Volunteers - Desi Marlizar (Journal of Education Research, 2026)
This study analyzes the problem of waste that continues to damage ecosystem the aesthetics of the West Aceh coastline. Although volunteers carry out routine cleaning efforts, the waste is scattered again after being cleaned. This reflects the low level of public awareness and partisipation that leads to a recurring cycle of pollution. This study uses a qualitative method with a descriptive approach. This study explores how public understanding and behavior towards waste and the environment are the result of social construction. If society collectively considers littering as normal and the waste management system does not form positive norms, then the reality of "dirty beaches" will continue. Therefore, this study aims to understand the existence and dynamics of the volunteer movement, as well as investigate public views on these actions.